Single Atom Catalysis for Hydrogen Evolution Reaction using Transition‐metal Atoms Doped g‐C3N3: A Density Functional Theory Study. Issue 7 (13th February 2023) - Zhang, Wenya; Huang, Zhijing; Gao, Zhaoju; Perez‐Aguilar, Jose Manuel; Gu, Zonglin; Tu, Yusong
Abstract: Single transition‐metal atom coordinated graphite carbon nitride, including the metal atom doped g‐C3 N4 system, displays catalytic activity comparable to that of the noble metal Pt catalyst with outstanding performance. Herein, we investigate the single atom catalytic performance of g‐C3 N3 embedded by a single transition metal atom (M−C3 N3 ; M=Mn, Fe, Co, Ni, Cu, Rh, Pd, Ag, and Pt) for hydrogen evolution reaction (HER) using density functional theory (DFT) calculations. The results indicate that all the M−C3 N3 catalysts are thermally and dynamically stable systems. By comparing the Gibbs free energies, we found that the Rh−C3 N3 catalyst exhibits the best HER electrocatalytic performance among the investigated systems. Subsequently, analysis of electronic structure indicates that the Rh−C3 N3 system displays a metallic behavior, which is a beneficial feature for an adequate HER electrocatalyst. Finally, the charge density difference of the Rh−C3 N3 structure further supports the rationality of our results. This study provides a new candidate of low‐cost, high‐performance, and highly active non‐noble metal electrocatalysts. Abstract : We have performed DFT calculations to explore the HER electrocatalytic activity of single transition‐metal atom doped g‐C3 N3 monolayer. Rh−C3 N3 catalyst showed the best HER electrocatalytic performance by compared with other metal atom doped g‐C3 N3 . This study provides a new candidate of low‐cost, high‐performance, and highly active non‐noble metal electrocatalysts.